Greek atomism and current atomic theory from the perspective of evolutionary epistemology - Cayo-Miguel, Wilmar (2021)
The present research work aimed to explain the dynamics between Greek atomism and current atomism from the perspective of evolutionary epistemology in the students of the Faculty of Education Sciences of UNHEVAL - 2020. Bearing in mind that the study of Evolutionary Epistemology should promote an adequate understanding of the development of science, we ask ourselves: What is the dynamics between Greek atomism and current atomism from the perspective of evolutionary epistemology in the students of the Faculty of Education Sciences of the UNHEVAL - 2020? The method used was the signing, which consisted of collecting information on the atomic theory proposed by Democritus and the current atomic theory, as well as on evolutionary epistemology; in the case of students, a survey was taken. The work is part of the type of basic research at a descriptive level. For the analysis of the results of the survey, the mode of each variable was determined, since these were part of the nominal scale, and then they were contrasted with the hermeneutical analysis of the bibliography. After the study, it was determined that there is a very complex evolutionary relationship between Greek atomism and current scientific atomism, about which the students of the Faculty of Biology, Chemistry and Environmental Sciences of UNHEVAL have partial knowledge.